Impact of degree of substitution of acetylated ofada rice starch polymer on the release properties of nimesulide microspheres (2016)
Nimesulide microspheres were prepared by the quasi-emulsion solvent diffusion method, using acetylated starches of the indigenous Ofada rice (Oryza glaberrima Steud) with degrees of substitution (DS) 1.42 and 2.62. A full 23 factorial experimental design was performed using DS (X1), drug:polymer ratio (X2) and polymer concentration (X3) as independent factors; size, entrapment, swelling and time taken for 80% drug release (t80) were the dependent variables. Contour plots were generated and data from the in vitro release studies were fitted to various kinetic models. Nimesulide microspheres were near spherical, sizes varying from 50.91±16.22 to 74.24±24.73μm for microspheres containing starch DS 1.42 and from 21.05±4.25 to 46.10±3.85μm for starch DS 2.62. Drug entrapment was 56.75±0.45 to 98.28±2.30%. DS had the greatest effect on the size, swelling and dissolution time (p = 0.01) which was confirmed by the contour plots. The interaction between factors DS and drug:polymer ratio (X1X2) had the greatest effect on the microsphere properties (p = 0.04). Drug release was fitted into the First Order, Higuchi and Korsmeyer models. Acetylated starch of Ofada rice DS 2.62 was found more suitable for the formulation of microspheres because of reduced size and swelling, higher entrapment and prolonged drug release.